2013
DOI: 10.1136/bmjopen-2012-002277
|View full text |Cite
|
Sign up to set email alerts
|

A national survey of the infrastructure and IT policies required to deliver computerised cognitive behavioural therapy in the English NHS

Abstract: ObjectiveThis study aimed to identify if patients have adequate access to Computerised Cognitive Behavioural Therapy (cCBT) programmes in all mental health trusts across England.DesignThe primary researcher contacted a targeted sample of information technology (IT) leads in each mental health trust in England to complete the survey.SettingTelephone, email and postal mail were used to contact an IT lead or nominated expert from each mental health trust.Participants48 of the 56 IT experts from each mental health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Posternak & Miller, 2001). In the stepped-care approach, it has been suggested that cCBT (or other evidence-based self-help) is offered as a first step for milder cases or to bridge the time between specialist care (Andrewes et al 2013). Thus, the question of whether cCBT can reduce waiting times may not be answered entirely through RCTs.…”
Section: Discussionmentioning
confidence: 99%
“…Posternak & Miller, 2001). In the stepped-care approach, it has been suggested that cCBT (or other evidence-based self-help) is offered as a first step for milder cases or to bridge the time between specialist care (Andrewes et al 2013). Thus, the question of whether cCBT can reduce waiting times may not be answered entirely through RCTs.…”
Section: Discussionmentioning
confidence: 99%
“…This is not unexpected for this sample of people recruited online. However, our recent national surveys of access to online resources via the NHS in Scotland (Kenicer, McClay and Williams, 2012) and England (Andrewes, Kenicer, McClay and Williams, 2013) has identified a lack of provision for those who do not have their own access to computers at home. In effect this means that those who are unemployed or older may have limited opportunity to access such resources.…”
Section: Anticipated Problems In Using Online Self-helpmentioning
confidence: 99%
“…From a broader perspective, it is important to consider barriers that impact the use of cCBT within health services. When exploring the infrastructure and information technology (IT) policies of the NHS in the United Kingdom, it was found that service users are limited by the number of computers they have access to [ 36 ]. It has also been highlighted that IT policies restricted the ability for NHS staff to provide ongoing guidance and support to potential cCBT users through, for example, contact via service user’s personal email account.…”
Section: Discussionmentioning
confidence: 99%